Potential for Nitrogen Fixation in the Fungus-Growing Termite Symbiosis - Sapountzis, Panagiotis; de Verges, Jane; Rousk, Kathrin; Cilliers, Magdeleen; Vorster, Barend J.; Poulsen, Michael (Frontiers in Microbiology, 2016)
Termites host a gut microbiota of diverse and essential symbionts that enable specialization on dead plant material; an abundant, but nutritionally imbalanced food source. To supplement the severe shortage of dietary nitrogen (N), some termite species make use of diazotrophic bacteria to fix atmospheric nitrogen (N2). Fungus-growing termites (subfamily Macrotermitinae) host a fungal exosymbiont (genus Termitomyces) that provides digestive services and the main food source for the termites. This has been thought to obviate the need for N2-fixation by bacterial symbionts. Here we challenge this notion by performing acetylene reduction assays of live colony material to show that N2 fixation is present in two major genera (Macrotermes and Odontotermes) of fungus-growing termites. We compare and discuss fixation rates in relation to those obtained from other termites, and suggest avenues of research that may lead to a better understanding of N2 fixation in fungus-growing and other termites.